A molecular defect causing fish eye disease: an amino acid exchange in lecithin-cholesterol acyltransferase (LCAT) leads to the selective loss of alpha-LCAT activity. - Funke, H (1991)
Epidemiological as well as biochemical evidence of recent years has established that a low plasma level of high density lipoprotein-cholesterol is a predictor for the risk of coronary artery disease. However, there is a heterogeneous group of rare familial disorders, characterized by severe high density lipoprotein deficiency, in which the predicted increased risk is not clearly apparent. One such disorder has been called fish eye disease to reflect the massive corneal opacification seen in these patients. In this report, we describe the biochemical and genetic presentation of two German fish eye disease homozygotes and their family members. Vertical transmission of a decrease in the specific activity of lecithin-cholesterol acyltransferase (EC 2.3.1.43) indicated that this enzyme was a candidate gene for harboring the defect responsible for this disorder. Direct sequencing of DNA segments amplified by the polymerase chain reaction (PCR) that encode the exons of the lecithin-cholesterol acyltransferase gene led to the identification of a homozygous mutation resulting in the substitution of threonine at codon 123 for an isoleucine residue in both individuals. Family analysis in an extended pedigree was used to establish a causal relationship between this mutation and the biochemical phenotype for fish eye disease. The homozygous presence of this mutation in two phenotypically homozygous members of an unrelated Dutch family with fish eye disease further supports this finding.